Retrieving Lost Histories: Spaces of Healing, Spaces of Liberation - Leon, University of Malaya, Malaysia, Carol; Koh, Universiti Tunku Abdul Rahman, Malaysia, Gladys (Asiatic: IIUM Journal of English Language and Literature, 2014)
A major theme in postcolonial fiction is the struggle to forget the traumas of colonisation and that is why issues related to memory and history frequently emerge in contemporary texts. Tan Twan Eng (1972-) is an acclaimed Malaysian author who deals with the theme of memory particularly with regard to the Chinese community in Malaya during the Japanese Occupation. Using ideas of space and spatiality, this study investigates the postcolonial reclamation of history and home through the medium of memory in The Gift of Rain (2008). In this context, the notion of space used by Tan includes the physical landscape and the psychological landscapes of memory and history. In The Gift of Rain, the memories of the characters are sometimes in conflict with official historical narratives. This article argues that the slipperiness between personal and public narrations of history opens up a space that allows for a renegotiation of identity and understanding of self.